Textural and Compositional Changes in the Lithospheric Mantle Atop the Hawaiian Plume: Consequences for Seismic Properties - Andréa Tommasi; Lucan Mameri; Marguerite Godard (Geochemistry, Geophysics, Geosystems, 2020)
Abstract We characterized the texture, composition, and seismic properties of the lithospheric mantle atop the Hawaiian plume by petrostructural analysis of 48 spinel peridotite xenoliths from four localities in three Hawaiian islands. Coarse‐porphyroclastic peridotites with variable degrees of recrystallization, recorded by growth of strain‐free neoblasts onto the deformed microstructure, predominate. Full evolution of this process produced equigranular microstructures. Some peridotites have coarse‐granular microstructures. Coarse‐granular and coarse‐porphyroclastic peridotites have strong orthorhombic or axial‐[100] olivine crystal‐preferred orientations (CPOs). Recrystallization produced some dispersion and, locally, changed the olivine CPO towards axial‐[010]. Enrichment in pyroxenes relative to model melting trends and pyroxenes with interstitial shapes and CPO uncorrelated with the olivine CPO imply refertilization by reactive melt percolation. The unusual spatial distribution of the recrystallized fraction, Ti enrichment, and Rare Earth Element fractionation in recrystallized, equigranular, and coarse‐granular peridotites support that these microstructures are produced by static recrystallization triggered by melt percolation. However, there is no simple relation between microstructure and chemical or modal composition. This, together with marked variations in mineral chemistry among samples, implies multiple spatially heterogeneous melt‐rock reaction events. We interpret the coarse‐porphyroclastic microstructures and CPO as representative of the original oceanic lithosphere fabric. Annealing changed the microstructure to coarse‐granular, but did not modify significantly the olivine CPO. Recrystallization produced moderate dispersion of the CPO. “Normal” oceanic lithosphere seismic anisotropy patterns are therefore preserved. Yet Fe enrichment, refertilization, and limited heating of the base of the lithosphere may reduce seismic velocities by up to 2%, partially explaining negative velocity anomalies imaged at lithospheric depths beneath Hawaii.